Isolation and diagnosis of Veillonella bacteria from dental root caries. - Shaker GHaze (College of Education for Pure Sciences, 2009)
ABSTRACT The present study was coducted to isolate and charactrize the bacterium Veillonella from dental root caries. Fifty (50) samples were collected from caries areas inside the oral cavity from patients with denal root caries visiting teaching hospital of college of dentistry in mosul university. The samples were cultured directly on selective medium (Rogosa agar) which inhibit growth of streptococci & diphtheroids present within the sample because the medium contains the two different antibiotics (Vancomycin & Streptomycin) also the medium support the growth of Veillonella because it contains Sodium Lactate which considered the substrate used for Obtaining energy & growth. fifteen isolates is a rate of (30%) was idenitified as Veillonella Spp. According to morphological features using Gram stain and colony morphology on selective medium when grown under obligate anaerobic condition and was found negative to cytochrome oxidase test, benzidene test and carbohydrate fermentation. The identification of bacterium was verified by exposing the bacterium to UV radiation (365nm) which resulted in a red flouresence. The isolates were not identified to the species level because it require modern genetic techniques not available to us like PCR-P and DNA-RNA sequence analysis.